Blue cheese breath and stinky feet how to deal with bullies - DePino, Catherine; Matthews, Bonnie 1963.; Beyl, Charles (Washington, D.C. Magination Press, 2004)
With the help of his teacher and his parents, Steve devises "The Plan", strategies for avoiding, defending against, and disarming a bully who has been tormenting him at school.
Keywords: Bullies -- Fiction